The influence of age on health valuations: the older olds prefer functional independence while the younger olds prefer less morbidity - Hofman CS (Dove Medical Press, 2015)
Cynthia S Hofman,1,2 Peter Makai,1 Han Boter,3 Bianca M Buurman,4 Anton J de Craen,5 Marcel GM Olde Rikkert,1 Rogier Donders,2 René JF Melis1 1Department of Geriatric Medicine, Radboud University Medical Center, Nijmegen, the Netherlands; 2Department for Health Evidence, Radboud University Medical Center, Nijmegen, the Netherlands; 3Department of Epidemiology, University of Groningen, University Medical Centre Groningen, Groningen, the Netherlands; 4Department of Internal Medicine, Section of Geriatric Medicine, Academic Medical Center, Amsterdam, the Netherlands; 5Department of Gerontology and Geriatrics, Leiden University Medical Centre, Leiden, the Netherlands Background: To assess the effectiveness of geriatric interventions, The Older Persons and Informal Caregivers Survey – Composite Endpoint (TOPICS-CEP) has been developed based on health valuations of older persons and informal caregivers. This study explored the influence of the raters’ age on the preference weights of TOPICS-CEP’s components.Methods: A vignette study was conducted with 200 raters (mean age ± standard deviation: 72.5±11.8 years; 66.5% female). Profiles of older persons were used to obtain the preference weights for all TOPICS-CEP components: morbidity, functional limitations, emotional wellbeing, pain experience, cognitive functioning, social functioning, self-perceived health, and self-perceived quality of life. The raters assessed the general wellbeing of these vignettes on a 0–10 scale. Mixed linear regression analysis with interaction terms was used to explore the effects of raters’ age on the preference weights.Results: Interaction effects between age and the TOPICS-CEP components showed that older raters gave significantly (P<0.05) more weight to functional limitations and social functioning and less to morbidities and pain experience, compared to younger raters.Conclusion: Researchers examining effectiveness in elderly care need to consider the discrepancies between health valuations of younger olds and older olds when selecting or establishing outcome measures. In clinical decision making, health care professionals need to be aware of this discrepancy as well. For this reason we highly recommend shared decision making in geriatric care. Keywords: general wellbeing, preferences, valuation, domains, composite endpoint, age